PERCEIVED ORGANIZATIONAL JUSTICE AND QUALITY OF WORK-LIFE OF ACADEMICS: THE MODERATING ROLE OF SELF-EFFICACY - Egwuenu, Rebecca Ngozi; Madubueze, Mmesomachukwu Favour (African Journal of Social and Behavioural Sciences, 2025)
This study explored the perceived organizational justice and quality of work-life of academics, examining the moderating role of self-efficacy. A cross-sectional survey design was adopted for the study, and a sample of 132 academics of the University of Delta, Agbor, participated in the study. Three standardized questionnaires were used for data collection, namely, Colquitt’s Organizational Justice Scale, Walton’s Quality of Work-life Scale, and the General Self-Efficacy Scale. Three hypotheses were formulated and tested using multiple regression, simple linear regression, and moderated regression analysis. Results showed a significant joint influence of perceived organizational justice on quality of work-life, and significant independent contributions of distributive justice and interpersonal justice whereas the results for procedural justice and informational justice were not significant. Furthermore, self-efficacy showed a significant influence on quality of work-life. However, the interaction term between organisational justice and quality of work-life was not significant. The overall model explained 37.8% of the variance in quality of work-life. Study findings imply that self-efficacy does not buffer or sufficiently compensate for institutional justice deficiencies. It was recommended that the universities prioritise equitable distribution of work and benefits.